Experimental Study on Behaviour of Rc T-Beam Strengthened with Jute Fiber Laminates - A Review - N, Tharunkumar; G, Anand (International Research Journal of Multidisciplinary Technovation, 2019)
The present investigation addresses the external strengthening of reinforced concrete (RC) T-beams using jute fiber laminates. An experimental study is mainly carried out to study the change in structural behaviour of RC T-beams using externally wrapped jute fiber laminates, to enhance the shear and flexural capacity of the beams. The effect of pattern and orientation of the strengthening fabric on the shear capacity of the strengthened beams will be examined. RC T-beams with minimum shear reinforcement is designed and then external confinement using jute fiber laminates is carried out using epoxy resin. The layer confinement is executed to study and analyze the behaviour of confined beams with respect to control beam. Experimental results showing the advantage of beam strengthened using the various lay-ups of jute fiber are to be discussed. For all developed composites, experimental results revealed that the tensile properties of the developed composites are strongly dependent on the tensile strength of jute fiber and that the tensile properties of jute fiber are very much defect sensitive. Jute as a natural fiber is eco-friendly, low cost, versatile in textile fields and has moderate mechanical properties, which replaced several synthetic fibers in development of many composite materials. However, the hydrophilic nature of the jute fiber affects the mechanical properties of the developed composites. As a result to arrest crack and improve the strength of beam.